2015
DOI: 10.1016/j.juro.2015.06.090
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Nerve Stimulation for Pediatric Lower Urinary Tract Dysfunction: Development of a Standardized Pathway with Objective Urodynamic Outcomes

Abstract: Sacral nerve stimulation is a treatment option that may produce significant improvement in objective and subjective measures of bladder function in children with refractory lower urinary tract dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…In 2015, Schober et al concluded significant improvement in voiding dysfunction scores and in urodynamic parameters in a group of 23 children with OAB. 75 Sacral neuromodulation might be a possibility for judiciously selected children with unmanageable OAB.…”
Section: Neuromodulationmentioning
confidence: 99%
“…In 2015, Schober et al concluded significant improvement in voiding dysfunction scores and in urodynamic parameters in a group of 23 children with OAB. 75 Sacral neuromodulation might be a possibility for judiciously selected children with unmanageable OAB.…”
Section: Neuromodulationmentioning
confidence: 99%
“…Information about improvement in urinary symptoms could not be assessed since this was not consistently reported for our ACE patients in the medical record. Although SNS is considered effective in treating urinary symptoms, 16,27 it would be interesting to compare results between SNS and ACE in children with FC. Moreover, the use of Malone as an antegrade option for FC at our institution became more widely available during the time span of this study.…”
Section: Discussionmentioning
confidence: 99%
“…One wonders, if this effect is sustained, perhaps future, adult LUTS with initial treatment in childhood could be altered or eliminated. Explant surveys for those explanted for cure and complication.^Raw scores in the cure cohort were 5,8,9,15,16. * Based upon cut-off score of 11 suggested by Afsar et al [12].…”
Section: Discussionmentioning
confidence: 99%